LATE TRIASSIC (EARLY-MIDDLE CARNIAN) CRUROTARSAN TRACKS FROM THE VAL SABBIA SANDSTONE (EASTERN LOMBARDY, BRESCIAN PREALPS, NORTHERN ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2009)
A new Late Triassic tetrapod tracksite was discovered north of the Zone village, on the north-eastern side of the Iseo Lake (Southern Alps, Brescia, Lombardy). The tracks are preserved on two distinct bedding planes, belonging to the lower/middle Carnian Val Sabbia Sandstone. The ichnoassemblage is composed of about seventy footprints, organized in six quadrupedal trackways exhibiting both wide and narrow gauge. All the trackways can be attributed to a crurotarsan archosaur trackmaker and at least three of them could be assigned with confidence to the ichnogenus Brachychirotherium Beurlen 1950. If we exclude a dubious Brachychirotherium specimen track from Mt. Pelmetto (Dolomites), the Zone material represents the first well documented report of this ichnogenus from the Upper Triassic of Northern Italy. The footprints have been analyzed both with traditional methods, and with 3D technologies, such as the terrestrial laser scanner. The ichnoassemblage, although not exceptionally preserved, adds new important data for the stratigraphic distribution of crurotarsan tracks in the Triassic of Southern Alps.
Keywords: Brachychirotherium; Chirotherian footprints; Late Triassic; Early/middle Carnian; Northern Italy